Resistive switching characteristics and mechanism of lanthanum yttrium oxide (LaYO3) films deposited by RF sputtering for RRAM applications - Cheng, Chiou-Ru; Tsai, Meng-Hung; Hsu, Tsung-Hsien; Li, Ming-Jen; Huang, Cheng-Liang (Journal of alloys and compounds, 2023)
LaYO3 thin films are deposited by using RF sputtering and resistive switching properties of LaYO3-based RRAM devices are investigated. Specifically, the effects of sputtering time, top electrode materials, deposition conditions, annealing temperature, and annealing processes on resistive switching characteristics of the devices are studied. The results indicate that conductive filaments are mainly dominated by oxygen vacancies whose concentration can be manipulated by the deposition atmosphere and annealing process. The formation of conductive filaments can be enhanced by the diffusion of In ions from an indium tin oxide substrate into LaYO3 layer during the annealing process. The Schottky barrier height under different top electrodes and deposition atmospheres also have an impact on the formation of filaments. In addition, post-metal anneal can help to form an AlOx interface layer, which plays significant roles in improving resistive switching performance of the LaYO3-based RRAMs. The devices annealed at 400 ºC possess resistive switching characteristics for over 1200 cycles and a Ron/Roff ratio of 103, showing promise for non-volatile memory applications. [Display omitted] •Oxygen vacancies dominating conductive filaments can be manipulated by the deposition atmosphere and annealing process.•The formation of conductive filaments can be enhanced by the diffusion of In ions•Schottky barrier heights under different electrodes and deposition atmospheres also have impacts on the formation of filaments.•The interface layer from annealing treatment plays significant roles in improving RS performance of the LaYO3-based RRAMs.